Relation Between the Corticospinal Tract State and Activities of Daily Living in Patients With Intracerebral Hemorrhage - Jang, Sung Ho; Choi, Eun Bi (Stroke (1970), 2022)
We investigated the relation between the ipsilesional corticospinal tract (CST) state and activity of daily living independence in patients with chronic intracerebral hemorrhage. Fifty-six consecutive patients with unilateral intracerebral hemorrhage and 38 healthy control subjects were recruited for this study. The Motricity index and the modified Barthel index were used to evaluate motor function of the affected extremities and activity of daily living independence, respectively. The diffusion tensor imaging parameter values for fractional anisotropy (FA) and voxel number (VN) of the CST were determined. Ratios of the ipsilesional to the contralesional CST measures were calculated and are presented as the CST-ratio (FA value and VN). The FA value and VN of the ipsilesional CST and the CST-ratio in the patient group were lower than those of the control group ( <0.05). There was a strong positive correlation between the Motricity index score of the affected extremities and the modified Barthel index score ( <0.05), while the FA value and VN of the ipsilesional CST and the CST-ratio showed moderate and strong positive correlations with the Motricity index and modified Barthel index scores, respectively ( <0.05). In addition, the VN of the ipsilesional CST showed excellent utility as a classifier, whereas the FA value of the ipsilesional CST and the FA value and VN of the CST-ratio showed good classifier utility ( <0.05). We demonstrated that impairment of activity of daily living independency was closely related to the injury severity of the ipsilesional CST in patients with chronic intracerebral hemorrhage. In addition, the injury severity of the ipsilesional CST can be used to classify the degree of activity of daily living independency. Registration: URL: http://www.e-irb.com/index.jsp; Unique identifier: 2021-03-014.